SYNOPSIS AND PROSPECTS OF AUTOIMMUNOLOGY DEVELOPMENT WORLDWIDE (AFTER THE MATERIALS OF THE 11th INTERNATIONAL CONGRESS IN LISBON, MAY 16-20, 2018). PROCEEDING I: FIRST ACADEMY OF AUTOIMMUNITY - E. A. Korneva (SPb RAACI, 2019)
A review article is an aftermath of the 11th International Congress on Autoimmunity and First Academy of Autoimmunity, happened 14th to 20th May, 2018 in Lisbon. The first part of paper discusses the formation, main problems and prospects for the development of Autoimmunology as a new integral branch of fundamental and clinical Medicine engaged in the research, diagnosis, treatment and prevention of autoimmune diseases of various organs and systems, totally circa 90 of them. A summary of all lectures conducted during the Academy of Autoimmunity is given, including a discussion of the newest and controversial aspects of the development of the modern concepts of the immune system, autoimmunity and autoimmune pathology. Article reviews data on the current problems of Immunology associated with the use of large databases of clinical and laboratory findings and extrapolation of animal experimentation data to humans. The newest ideas about congenital immunity, including the populations of innate lymphoid cells, on the role of various groups of receptors of the innate immunity system, on the participation of the mechanisms of innate immunity in pathogenesis of autoimmune disorders are highlighted. Modern concepts of antigen presentation are offered, including classification of dendritic cells, alternative pathways of macrophage activation, as well as on costimulatory and inhibitory interactions of ligands and receptors of lymphocytes and antigen-presenting cells. The latest data about the subpopulations of T lymphocytes and their role, including the functions of Tfh cells and the relationships of these subpopulations with various immune responses are highlighted. Influence of microbiota on T cell subpopulations is discussed. The main regularities of the phenomenon of immunological memory are formulated. The questions of antibody production and B lymphocyte functions are considered taking into account recently discovered mechanisms of intracellular penetration of immunoglobulins and details of affinity maturation of lymphoid clones. The new therapeutic approaches in the treatment of autoimmune diseases associated with influences on B and T lymphocytes are described. Mechanisms of central and peripheral autotolerance have been highlighted, taking into account data on the function of the AIRE gene and T regulators. The role of T regulators in placentation is considered. The role of interleukin-2 and its recombinant analogues in immune interactions is interpreted in a new way, taking into account not only their immunostimulating, but, under certain conditions, immunosuppressive potential also. Considerable attention has been paid to the inhibitory receptors of T lymphocytes and to immuno-biotherapeutic effects on them. The history and current status of Oncoimmunology and the use of blockers of inhibitory T lymphocyte receptors in Oncology, including the side effects of treatment with check-point inhibitors, are briefly discussed. Information was given on the held on 21-23 September 2018 2nd Academy of Autoimmunity in St. Petersburg.